Awareness of diabetic nephropathy in patients with type 2 diabetes mellitus: the Indian scenario - Chirag Bansal; Reshma Kaushik; Rajeev Mohan Kaushik (Society of Diabetic Nephropathy Prevention, 2018)
Introduction: Diabetic nephropathy is an important complication of diabetes mellitus leading to significant morbidity and mortality. Objectives: To study the awareness of diabetic nephropathy in patients with type 2 diabetes mellitus (T2DM) and the factors influencing patient awareness of diabetic nephropathy. Patients and Methods: Four hundred subjects, aged above 18 years with T2DM as per American Diabetes Association (ADA) criteria, were selected. Patient awareness regarding diabetic nephropathy was assessed as per a prefixed questionnaire. Results: Awareness of basic information concerning diabetes was present in more than 60% of patients. No significant differences were seen between awareness scores of male and female (P = 0.385), rural and urban (P = 0.120) and literate and illiterate (P = 0.567) diabetic patients. Awareness scores were higher in diabetic patients exceeding 50 years of age (P = 0.004) and patients having diabetes for more than10 years (P < 0.0001), controlled diabetes (P = 0.026) and diabetic nephropathy (P < 0.0001). Awareness of diabetic nephropathy was independently associated with duration of diabetes (P = 0.010) and diabetic nephropathy (P = 0.011) but not with age (P = 0.754) and control of diabetes (P = 0.229). Conclusion: A substantial proportion of diabetic patients are still unaware of the basic facts about diabetes and diabetic nephropathy. Awareness of diabetic nephropathy depended upon duration of diabetes and presence of diabetic nephropathy and requires promotion during early stages of diabetes to improve control of diabetes and prevent diabetic nephropathy.